Retrieving the times series of input data for assessment of NEA saithe - Fotland, Åge; Mehl, Sigbjørn (ICES, 2010)
Working Document # 5 Arctic Fisheries Working Group, Lisbon, 22-28 April 2010. This WD is meant as an explanation to how the times series input files for the assessment of NEA saithe is expanded to age 15+ at the 2010 AFWG. Table 3 and 4 includes age group 2. This age group is not used in the current assessment.